2016
DOI: 10.3946/kjme.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Complex and novel determinants of empathy change in medical students

Abstract: Purpose:Physician empathy is a core attribute in medical professionals, giving better patient outcomes. Medical school is an opportune time for building empathetic foundations. This study explores empathy change and focuses on contributory factors.Methods:We conducted a cross-sectional study involving 881 students (63%) from Years 1 to 5 in a Singaporean medical school using the Jefferson Scale of Physician Empathy-Student version (JSPE-S) and a questionnaire investigating the relationship between reported and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 30 publications
3
55
1
3
Order By: Relevance
“…Regarding the engagement in extracurricular activities, the EI was significantly higher among those involved in aesthetic activities than those who did not but no significant difference was observed among those who did and did not participate in sports activities. A study done in medical students in Singapore has found that those who spent more time on art had higher empathy scores [ 32 ]. Despite the common belief, factors such as not having siblings, family income and religiosity did not have a significant effect on the EI.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the engagement in extracurricular activities, the EI was significantly higher among those involved in aesthetic activities than those who did not but no significant difference was observed among those who did and did not participate in sports activities. A study done in medical students in Singapore has found that those who spent more time on art had higher empathy scores [ 32 ]. Despite the common belief, factors such as not having siblings, family income and religiosity did not have a significant effect on the EI.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies done in other countries about the relationships among medical student burnout, empathy, work value, and professionalism [ 19 - 22 ]. This study was aimed at examining the relationship between medical students’ academic burnout and their empathy, and determining whether a sense of calling serves as a mediating variable in the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although international healthcare education, training and work practices are highly variable, there are common themes, and empathy decline in non-UK health systems has been widely reported. 27 - 30 Accordingly, the results may be of value to international educators who are seeking to arrest empathy decline in their healthcare education system.…”
Section: Introductionmentioning
confidence: 99%